2022
DOI: 10.3389/fpls.2022.1008829
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel regulation of anthocyanin-promoting R2R3-MYB transcription factors in plants

Abstract: Anthocyanins are common secondary metabolites in plants that confer red, blue, and purple colorations in plants and are highly desired by consumers for their visual appearance and nutritional quality. In the last two decades, the anthocyanin biosynthetic pathway and transcriptional regulation of anthocyanin biosynthetic genes (ABGs) have been well characterized in many plants. From numerous studies on model plants and horticultural crops, many signaling regulators have been found to control anthocyanin accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 148 publications
(214 reference statements)
0
9
0
Order By: Relevance
“…R2R3-MYBs are the major determinant regulators of the MBW(MYB-bHLH-WD40) complex, which fine-tune the spatial and temporal localization of anthocyanins by regulat-ing the expression level of flavonoid biosynthesis pathway genes [17,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R2R3-MYBs are the major determinant regulators of the MBW(MYB-bHLH-WD40) complex, which fine-tune the spatial and temporal localization of anthocyanins by regulat-ing the expression level of flavonoid biosynthesis pathway genes [17,73].…”
Section: Discussionmentioning
confidence: 99%
“…Plant R2R3-MYB genes perform crucial roles in various biological processes, including plant growth and development, cell differentiation, specialized secondary metabolism, and biotic and abiotic stress responses [14,15]. In particular, many R2R3-MYB genes have been thoroughly investigated and verified to regulate tissue-specific anthocyanin accumulation in various plants [16][17][18]. For example, the first R3R3-MYB plant gene, COLORED1 (C1), which was isolated from maize, encodes a regulatory protein to control anthocyanin pigment production in the aleurone layer of the endosperm [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…MYB30, MYB80, MYB86, MYB102) and an ANR (arahy.IK60LM) were found to be hub genes involved in anthocyanin and proanthocyanin metabolism by WGCNA. Previous study showed that R2R3-MYB transcription factor and ANR were important regulatory genes that confer pigment accumulation in plant tissues (Yang et al, 2022). A major gene (AhTc1) controlling peanut purple testa was characterized to be encoding a R2R3-MYB transcription factor using QTL-seq method together with transcriptome analysis and gene expression profiling.…”
Section: Myb-like Transcription Factors and Anr Play Vital Roles In S...mentioning
confidence: 99%
“…MYB-mediated anthocyanin biosynthetic pathway of fruit can be affected by a variety of elements, including light, low temperature, and hormone signal transduction pathways [ 21 ]. Earlier studies showed that relevant TFs and structural genes associated with the anthocyanin biosynthesis are activated to express in plants in response to low temperature [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed that relevant TFs and structural genes associated with the anthocyanin biosynthesis are activated to express in plants in response to low temperature [ 22 , 23 ]. Cold-activated MBW complexes are created through the up-regulation of critical positive genes of anthocyanin biosynthesis [ 21 ]. In addition, various TFs can interact with the MBW complex in the regulation of anthocyanin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%